ANALISIS RISIKO PAJANAN SIANIDA PADA MASYARAKAT DESA NGEMPLAK KIDUL KECAMATAN MARGOYOSO KABUPATEN PATI - Iinaas Adzkiya Tsani; Sulistyani Sulistyani; Budiyono Budiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Tapioca industrial liquid waste has a high cyanide content of 44.40 mg/l. That cyanide content exceeds the cyanide quality standard in tapioca waste water which is 0.3 mg/l. The cyanide content can infiltrate in dug wells that are used as a source of clean water and drinking water for the community around the tapioca industry. The dug well water used as a source of drinking water has cyanide levels of 0.2 - 0.5 mg/l with a well distance of 0-25 m from the tapioca industry. It is necessary to calculate health risks in the community around the tapioca industry due to exposure of cyanide. The purpose of this study was to analyze environmental health risks due to exposure of cyanide in the community in the tapioca industrial area of Ngemplak Kidul, Margoyoso District, Pati Regency. This type of research was an observational descriptive study with an Environmental Health Risk Analysis (EHRA) approach. The sample in this study were 30 subjects and 30 samples drinking water. The results showed that the average level of cyanide in drinking water was 0.0024 mg/l. The average rate of drinking water intake was 1.7 liters, the frequency of exposure was 364.2 days/year, duration of exposure was 16.23 years, and body weight was 58.76 kg. Data analysis using EHRA obtained RQ 0.06 results in a duration of 16.23 years, and RQ 0.12 at a duration of 30 years. The conclusion was that cyanide levels in the respondent's drinking water in accordance with quality standards and the level of risk of realtime and lifetime exposure of non-carcinonegic effects are still declared safe (RQ <1). The calculation of the estimated risk of exposure to cyanide of non-carcinogenic effects at the 15, 30, and 60 years is also still safe (RQ <1). Further analysis of environmental health risks were needed by measuring cyanide intake comprehensively which considers other exposure pathways.